2007
DOI: 10.1002/adfm.200600564
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Nanoparticles Based Fabrication of Gecko Foot‐Hair‐Inspired Polymer Nanofibers

Abstract: Wafer‐scale polymer nanofabrillar structures have been fabricated using the combination of colloidal nanolithography, deep‐silicon etching, and nanomolding to mimic the nanostructure of gecko foot‐hairs. The artificial surface features densely packed polymeric nanofibrils with super‐hydrophobic, water‐repellent, and “easy‐to‐clean” characteristics. The lateral dimension of the nanofibrils is as small as 250 nm and an aspect‐ratio as high as 10:1 has been achieved without lateral collapse between neighboring fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 49 publications
2
80
0
Order By: Relevance
“…Multiwalled carbon nanotubes (MWCNT; Zhao et al 2006;Ge et al 2007) and low aspect ratio (length/ diameterZ0.5-10) hard polymer stalks (Geim et al 2003) demonstrated tensile adhesion but they require high normal compressive preload. Kustandi et al (2007) have recently demonstrated 0.7 N cm K2 tensile adhesion with preload pressure of 1 N cm K2 using 10 : 1 aspect ratio hard polymer fibres (Ew2.8 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…Multiwalled carbon nanotubes (MWCNT; Zhao et al 2006;Ge et al 2007) and low aspect ratio (length/ diameterZ0.5-10) hard polymer stalks (Geim et al 2003) demonstrated tensile adhesion but they require high normal compressive preload. Kustandi et al (2007) have recently demonstrated 0.7 N cm K2 tensile adhesion with preload pressure of 1 N cm K2 using 10 : 1 aspect ratio hard polymer fibres (Ew2.8 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of lithography and the two-step molding process is now also widely used for fabricating hierarchical fibrillar surfaces [37, 110−112]. Deep reactive ion etching [113], self-assembly [114], anodic oxidation [113], angled etching, and mechanical yielding techniques or methods [37, 115−117] have also been explored to fabricate templates of gecko-inspired dry adhesive surfaces.…”
Section: Fabrication Of Gecko-inspired Surfaces With Strong Adhesionmentioning
confidence: 99%
“…A selection of materials for gecko-inspired adhesives, such as polymide [89,106], PVS [25,74], PDMS [99,106,108,126], poly(methyl methacrylate) (PMMA) [115], polyurethane [109][110]113], polystyrene (PS) [105,114], silicon rubber [127], polypropylene [128], and polyethylene has also been considered [122]. It is proposed that polyurethane with a low Young's modulus can generate strong adhesion because the polar groups contribute to the enhancement of the adhesion; thus, this material may be suitable for gecko-inspired adhesives [129].…”
Section: Fabrication Of Gecko-inspired Surfaces With Strong Adhesionmentioning
confidence: 99%
“…Various strategies have been formulated to synthesize gecko feet-like surfaces from different materials including silicones [75], CNTs [76 -79], poly(methyl methacrylate) [80], polyurethane acrylate [81], polydimethylsiloxane (PDMS) [82] and more [83][84][85][86]. The successful fabrication of gecko-inspired functional materials requires the combination of the physical, chemical and biological principles.…”
Section: Self-cleaning Without Watermentioning
confidence: 99%